‘Life After Delivery’:: a phenomenological enquiry into one woman’s experience - Sabel, Vivien (European Journal for Qualitative Research in Psychotherapy, 2011)
The massive shifts in emotions and upheaval of social roles women are likely to experience following the birth of a child have been well documented. And yet, it is still not possible to predict how each in- dividual woman will respond. This research explores one woman’s experience using a phenomenologi- cal, relational-centred research approach. My aim was to try to witness and ‘give voice to’ her unique, special and particular experience of life after delivery in a relatively unstructured interview. Analysis revealed four emergent themes: Protection-Desertion; Contact-Isolation; Belonging-Shame; and Anxi- ety-Ambivalence. Throughout the interview there was a sense that Kate wished to be seen as the same as other mothers, rather than as a ‘mother-with-deficits’. She goes to some lengths to hide herself from her family and professionals to give them no reason to doubt her ability.